Social Conflict from The Perspective of Alan Torn and Pierre Bourdieu: A theoretical study - Shahlaa Wali Jabbar; Dunya Saladin Mirdan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The subject of conflict is an important and essential subject in sociology, and has been much debated by classical and modern theorists. The concept of social conflict has now changed in terms of its understanding and references, so that new theorists have analyzed the concept of conflict from other dimensions, including Alan Thorne and Pierre Bourdieu. The main theme of this study is to present the most important factors that play a role in the formation of social conflict among social groups and the variables that surround them, of course, from the perspective of the French scientists Alain Thorne and Pierre Bourdieu. The importance of this study lies in the fact that the issue of conflict has been constantly debated and interpreted from different dimensions by social theorists, some linking it to class issues, others to intergenerational conflict, and others to other concepts. As times have changed, the understanding and analysis of the concept has changed and its symbols have changed. The importance of the available research is that it focuses on the issue of conflict from the perspective of two contemporary theorists, Alan Thorne and Pierre Bourdieu, who have played a significant role in advancing the theoretical foundations of sociology. The aim of this study is to identify the dimensions of social conflict from the perspective of Alan Thorne and Pierre Bourdieu and to analyze the signs of social conflict in the present era.